The Relationship Between Self-Efficacy and Zinc Intake and Academic Achievement Among Junior High School Students - Aghniya Intan Ridhoputrie; Mohammad Shoim Dasuki (Jurnal Sehat Indonesia (JUSINDO), 2026)
Academic achievement among junior high school students is influenced by various internal factors, particularly psychological factors such as self-efficacy and physiological factors such as adequate zinc intake, both of which play important roles in learning motivation and cognitive function. This study aimed to analyze the association between self-efficacy and zinc intake and academic achievement among junior high school students. This quantitative observational analytic study employed a case-control design and was conducted among eighth-grade students at SMP in PK Surakarta from October to December 2025. A total of 94 students were selected using purposive sampling. Self-efficacy was measured using the General Self-Efficacy Scale (GSES), zinc intake was assessed using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and academic achievement was determined based on Mid-Semester Summative Assessment scores. Data were analyzed using univariate analysis, bivariate analysis with the Chi-square test, and multivariate analysis using binary logistic regression. Low self-efficacy was associated with poor academic achievement (p = 0.032; OR = 2.567; 95% CI: 1.075–6.131), while low zinc intake showed a stronger association with poor academic achievement (p < 0.001; OR = 9.103; 95% CI: 2.456–33.708). In multivariate analysis, both zinc intake and self-efficacy were significantly associated with academic achievement. Zinc intake and self-efficacy were associated with academic achievement among junior high school students.